Politik Indonesia Tahun 1990-an: Kebangkitan Ideologi? - Saiful Mujani (Studia Islamika, 1996)
This article is a review of the book Politics in Indonesia : Democracy , Islam and the Ideology of Tolerance written by Douglas E. Ramage . This book is the result of research that lasted from 1990-1994 , a period characterized much political debate and move groups of Indonesia, including from Islamic groups . The problem is studied from this book is a discourse about Pancasila as interpreted by these groups with all the implications of the widespread national problem .According to Ramage , initially it looked Pancasila as an ideology that is not interesting , nothing more than a tool of legitimacy of the New Order power elite . But after carefully considered , as it turns out wrong impression . Pancasila has turned out to be an interesting and important discourse studied . Pancasila turned out to be above the interests of the power elite . He became a central discourse in Indonesian politics , involving a variety of groups and interests . The debate over the interpretation of Pancasila inevitableDOI: 10.15408/sdi.v3i1.817